An update on drug development for the treatment of nonalcoholic fatty liver disease – from ongoing clinical trials to future therapy. Issue 3 (4th March 2021) - Rau, Monika; Geier, Andreas
ABSTRACT: Introduction: Nonalcoholic fatty liver disease (NAFLD) represents an increasingly recognized disease entity with rising prevalence of 25% in the general population. Given the epidemic increase, regulatory agencies have defined an unmet medical need and implemented initiatives to expedite the development of drugs for NASH treatment. Areas covered: Literature search in Medline and worldwide web was accessed latest in 23.01.2021. In recent years new drugs acting on various pathophysiological processes in NASH have entered clinical development. These drugs combine beneficial metabolic effects with anti-inflammatory and anti-fibrotic effects to treat NASH. Current drug classes being investigated for NASH treatment are agonists of nuclear receptors such as FXR agonists (including FGF19), PPAR agonists, chemokine receptor inhibitors, thyroid hormone receptor-ß agonists and analogues of enterohepatic hormones including GLP-1 and FGF21 or SGLT2 inhibitors. Expert opinion: Obeticholic acid is the only drug with significant benefit in the phase 3 interim results and remains the candidate for first conditional approval as a NASH therapeutic. However, monotherapy with these drugs leads to a histological resolution of NASH in less than one-third of patients in recent trials. Therefore, the future of NASH therapy will putatively be a combination therapy of two different drug classes with complementary effects.